Integrating morphological and genetic data at different spatial scales in a cosmopolitan marine turtle species: challenges for management and conservation. Issue 2 (8th July 2020) - Álvarez-Varas, Rocío; Heidemeyer, Maike; Riginos, Cynthia; Benítez, Hugo A; Reséndiz, Eduardo; Lara-Uc, Mónica; Godoy, Daniel A; Muñoz-Pérez, Juan Pablo; Alarcón-Ruales, Daniela E; Vélez-Rubio, Gabriela M; Fallabrino, Alejandro; Piovano, Susanna; et al.
Abstract: Patterns of genetic structure in highly mobile marine vertebrates may be accompanied by phenotypic variation. Most studies in marine turtles focused on population genetic structure have been performed at rookeries. We studied whether genetic and morphological variation of the endangered green turtle ( Chelonia mydas ) is consistent geographically, focusing on foraging grounds. An association between population genetic structure and body shape variation at broad (inter-lineage) and fine (foraging grounds) scales was predicted and analysed using mitochondrial DNA and geometric morphometrics. Although genetic and phenotypic differentiation patterns were congruent between lineages, no fine-scale association was found, suggesting adaptive divergence. Connectivity among Pacific foraging grounds found here suggests that temperatures of ocean surface currents may influence the genetic structure of C. mydas on a broad scale. Our results suggest that vicariance, dispersal, life-history traits and ecological conditions operating in foraging grounds have shaped the intraspecific morphology and genetic diversity of this species. Considering a range of geographic and temporal scales is useful when management strategies are required for cosmopolitan species. Integrating morphological and genetic tools at different spatial scales, conservation management is proposed based on protection of neutral and adaptive diversity. This approach opens new questions and challenges, especially regarding conservation genetics in cosmopolitan species.